The Effect of Midazolam on Prevention of Post-Dural-Puncture Headache - Kashipazha, Davood; Babadi, Mansoureh (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: Post-dural-puncture headache (PDPH) is the most common side effect associated with a lumbar puncture (LP). The present study aims to evaluate the effect of midazolam on the prevention of PDPH. Methods: This single-blind randomized clinical trial study was performed on 120 patients aged 18-60 years who were candidates for diagnostic LP in 2017-2018. In the intervention group (n=30), 3 mg of midazolam was injected intravenously for two minutes 5-10 minutes before LP, and the control group received normal saline as placebo. Patients in both groups were evaluated and compared with each other in terms of incidence, onset, severity, and duration of PDPH. Results: The incidence of PDPH was lower in the midazolam group, but the difference was not significant (P>0.05). Mean severity, onset time, and duration of PDPH were not significantly different between the two groups (P<0.05). All patients in the intervention group and 75% of patients in the control group with PDPH had a history of headache. There was no significant difference between gender, mean age, BMI, pressure and CSF volume in patients with PDPH (P>0.05). The mean age of patients with PDPH was significantly lower in both groups, and the percentage of women with PDPH was considerably higher than that of men (P<0.05). Conclusion: Although there was no significant difference between the parameters studied in the two groups, patients with less age, history of headache, lower CSF pressure, and female gender were more likely to develop PDPH.